White noise - DeLillo, Don (London : Picador, 2011)
A brilliantly black and funny novel about humanity's greatest fear - death.
Originally published: New York: Viking, 1984; London: Picador, 1985.
ENH
Karim International
Keywords: Industrial accidents -- Fiction; College teachers -- Fiction; Middle West -- Fiction; English literature